Kinayah sebagai Instrumen Hukum dalam al-Qur’an: Telaah Ushul Fikih terhadap Makna Tersirat dalam Teks Syar’i - Fatimah, Nurul; F, Fatmawati; Abidin, Zaenal (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The language of the Qur’an does not only convey teachings explicitly but also employs indirect expressions such as kināyah, especially in delivering legal messages with ethical values. This study explores how kināyah functions as a legal tool in the Qur’anic discourse, using the methodology of uṣūl al-fiqh and thematic analysis of specific verses. By examining verses such as al-Baqarah 2:228, 2:187, and 2:235, it becomes evident that kināyah serves as a means of conveying legal rulings while maintaining ethical sensitivity and social decorum. The study demonstrates that kināyah can shape a more refined understanding of Islamic law without losing its normative implications.